Z-Source Drive Inverter using modified SVPWM for low Output Voltage and regenerating Operation - Lechler, Martin; von Zimmermann, Moritz; Piepenbreier, Bernhard (EPE 2009 Barcelona, 2009)
Z-source inverters, consisting of both inductors and capacitors as DC-link components, provide unique boost capability with simple structure needing no additional switching elements. Due to complex operation modes of the Z-source inverter compared to a conventional inverter, boost operation, light load and regenerating operation cannot be achieved using common space-vector pulse width modulation. This paper proposes a modified SVPWM, derived from the known equations, to overcome this limitation. Besides, equations to control the output behaviour for all operating modes, such as buck, boost and regenerating operation, are given in detail. Finally, experimental results are presented.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEEAS.zsourc
Keywords: AC/AC converter; Adjustable speed drive; Drive; Emerging topology